PENGARUH BERBAGAI DOSIS PUPUK ORGANIK CAIR LIMBAH RUMAH TANGGA TERHADAP PERTUMBUHAN DAN HASIL TANAMAN PADI GOGO - Izni Izni; Aris Aksarah Pas; Jumardin Jumardin (FAKULTAS PERTANIAN UNIVERSITAS ALKHAIRAAT, 2019)
This study aims to study the growth response and yield of gogo rice at various doses of household waste organic fertilizer. This study uses a randomized block design (RAK) of one factor. Grouping based on sunlight. The treatment that was tried was various doses of household organic liquid fertilizer (POC), namely, POC0 = without POC, POC1 = 200 ml / plant, POC2 = 250 ml / plant, POC3 = 300 ml / plant. The results showed that the treatment of various doses of liquid organic fertilizer had a significant effect on the growth and yield of gogodan rice and the treatment dose of 300 ml / plant had a higher effect compared to other treatments on the growth and yield of gogo rice plants.